The Role of Islamic Leadership, Organizational Culture, and Computer Anxiety in Improving Teacher Performance - Nur Fu' aidah, Alifta Luluk; Hartono, Sri; Wijianto, Wijianto (Nomico, 2025)
This study aims to analyze the influence of Islamic leadership, organizational culture, and the effect of computer anxiety on teacher performance at SMP Negeri 5 Ponorogo. The subjects in this study were all teachers at SMP Negeri 5 Ponorogo located at Jl. Dr. Soetomo, No. 11, Bangunsari, Ponorogo District, Ponorogo Regency, East Java. The sampling technique in this study used saturated sampling with a population of 65. Data collection techniques used in this study were interviews, observations, and questionnaires. The data analysis method used was multiple linear regression analysis with the SPSS program version 25.00. The results of the study showed that the Islamic Leadership variable had a significant effect on teacher performance at SMP Negeri 5 Ponorogo. The organizational culture variable had a significant effect on teacher performance at SMP Negeri 5 Ponorogo. The effect of computer anxiety variable had a significant effect on teacher performance at SMP Negeri 5 Ponorogo. The Islamic Leadership variable, organizational culture, and the effect of computer anxiety had a significant effect on teacher performance at SMP Negeri 5 Ponorogo